Endocytic Trafficking of DMP1 and GRP78 Complex Facilitates Osteogenic Differentiation of Human Periodontal Ligament Stem Cells - Merkel, Annette; Chen, Yinghua; George, Anne (Frontiers in Physiology, 2019)
Periodontal ligament contains periodontal ligament stem cells that maintain tissue homeostasis. Targeting hPDLSCs (human periodontal ligament cells) is a promising strategy for repair and regeneration of bone tissue destroyed by periodontal diseases. However, the mechanisms by which PDLSCs differentiate into osteoblasts to form a mineralized matrix is unclear. In this study, we demonstrate for the first time the molecular events that contribute to osteogenic differentiation of PDLSCs. Dentin matrix protein 1 (DMP1) and its receptor, Glucose regulated protein-78 (GRP78), are localized in the progenitor cells of the PDL. Our overall goal is to demonstrate the formation of DMP1-GRP78 complex at the plasma membrane and subsequent protein trafficking and nuclear localization to promote osteogenic differentiation. To study the internalization and routing of the complex, we mimic an in vivo differentiation scenario by stimulating cells with DMP1 and culturing them in the presence of osteogenic differentiation conditions. We first demonstrate the translocation of the ER chaperone protein GRP78 to the plasma membrane during the differentiation process. Total internal reflection microscopy imaging demonstrates the formation and internalization of the receptor- ligand (GRP78-DMP1) complex. Confocal microscopy results show the internalization of the GRP78-DMP1 complex specifically through the caveolin pathway and trafficked through the cell with various endocytic markers such as Rab5 and 7 GTPases to early and late endosomes respectively. DMP1 is ultimately transported to the nucleus where it functions to promote osteogenic differentiation as demonstrated by quantitative Real-Time PCR. This observation is the first report that suggests DMP1 and GRP78 can interact at the plasma membrane, then packaged in vesicles and ultimately DMP1 is routed to the nucleus where it aids in osteogenic differentiation of PDLSCs. Characterizing the osteogenic potential of PDLSCs would favor the development of therapeutic strategies for reconstruction of mineralized tissues destroyed by periodontal diseases.